Effects of plyometric training on skill and physical performance in healthy tennis players: a systematic review and meta-analysis - Deng, Nuannuan; Soh, Kim Geok; Huang, Dandan; Abdullah, Borhannudin; Luo, Shengyao; Rattanakoses, Watnawat (Frontiers Research Foundation, 2022)
Background: Plyometric training (PT) has been researched extensively in athletic populations. However, the effects of PT on tennis players are less clear. Methods: We aim to consolidate the existing research on the effects of PT on healthy tennis players’ skill and physical performance. On 30th May 2022, a comprehensive search of SCOPUS, PubMed, Web of Science, and SPORTDiscus (via EBSCOhost) databases was performed. PICOS was employed to define the inclusion criteria: 1) healthy tennis players; 2) a PT program; 3) compared a plyometric intervention to a control group or another exercise group, and single-group trials; 4) tested at least one measures of tennis skill or physical performance; and 5) non-randomized study trials and randomized control designs. Individual studies’ methodological quality was evaluated by using the Cochrane RoB-2 and ROBINS-I instruments. Using Grading of Recommendations Assessment, Development, and Evaluation (GRADE), the certainty of the body of evidence for each outcome was assessed, and Comprehensive Meta-Analysis software was employed for the meta-analysis. Results: Twelve studies comprising 443 tennis players aged 12.5–25 years were eligible for inclusion. The PT lasted from 3 to 9 weeks. Eight studies provided data to allow for the pooling of results in a meta-analysis. A moderate positive effect was detected for PT programs on maximal serve velocity (ES = 0.75; p < 0.0001). In terms of measures of physical performance, small to moderate (ES = 0.43–0.88; p = 0.046 to < 0.001) effects were noted for sprint speed, lower extremity muscle power, and agility. While no significant and small effect was noted for lower extremity muscle strength (ES = 0.30; p = 0.115). We found no definitive evidence that PT changed other parameters (i.e., serve accuracy, upper extremity power and strength, reaction time, and aerobic endurance). Based on GRADE, the certainty of evidence across the included studies varied from very low to moderate. Conclusion: PT may improve maximal serve velocity and physical performance components (sprint speed, lower extremity muscular power, and agility) for healthy tennis players; however, more high-quality evidence about the effects of PT on the skill and physical performance of tennis players merits further investigation. Systematic Review Registration: [https://inplasy.com/], identifier [INPLASY202250146].